KEMAMPUAN PEMECAHAN MASALAH MELALUI PENERAPAN STRATEGI THINKING ALOUD PAIR PROBLEM SOLVING PADA SISWA KELAS X MAN 2 PEKANBARU KAMPUS 2 - Febrina, Viona; Azizahwati, Azizahwati; M. Rahmad, M. Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research aims to describe the problem solving skill of student in class X-2 MA Negeri 2 Pekanbaru Campus 2 with the implementation of Strategy Thinking Aloud Pair Problem Solving in lesson impulse and momentum. The research used pre-experimental with one-shot case study design. The subjects were students of class X-2 totalling 29 students, consisting of 10 male students and 19 female students. The instrument of data collection in this study is the problem solving ability test consists of 4 essay questions. Analysis of the data in this study is a descriptive analysis to see an overview of the problem solving skill of student by using the criteria of the level of problem solving skills . The research showed the problem solving skill of student in class X-2 MA Negeri 2 Pekanbaru with the implementation of Strategy Thinking Aloud Pair Problem Solving in lesson impulse and momentum are at a low level. For every step of Problem Solving Skill of student showed that students at the step of understand the problem are at a very high level. For the step of devising a plan and carry out a plan are at a high level and then at looking back at the completed solution are at a very low level. Therefore in teaching physics, by using Thinking Aloud Pair Problem Solving could train problem solving skill of student but not effective.Key word : Thinking Aloud Pair Problem Solving, Problem Solving Skill